RETRAKSI: Analisis Parameter Fisika-Kimia untuk Kepentingan Rehabilitasi Ekosistem Mangrove di Pesisir Pulau Bungkutoko Kota Kendari - Yasin, Asramid; Pristya, Terry Y. R. (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2020)
Retraction NotificationAfter going through a careful process of review and attention to the article that have been published in Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, Volume 17 Issues 1 pp 1-18 in March 2020, the editor board decided to retract this article because of its violence to the Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan's ethical code.This article has been submitted at the same time in the Journal of Green Growth and Environmental Management. Before being published, we have made an effort to detect plagiarism using the turnitin application twice, on 30 November 2019 (23% of similarity) and 30 August 2019 (18% of similarity). On January 2, 2020, the corresponding author corrected and editted the article and the Editor published the article in the "Article in press" issue. Subsequently, the article was published in Volume 17 No. 1 of March 2020.We have corresponded with the authors and the authors declare their willingness to revoke their articles at Jurnal Green Growth dan Manajemen Lingkungan. As long as the article has not been revoked from the Jurnal Green Growth dan Manajemen Lingkungan, the document and its contents removed from the Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan.AbstractIn Southeast Sulawesi rehabilitation of mangrove areas that have been damaged but in reality not all mangrove rehabilitation activities were successful, this was allegedly caused by a mismatch in the type of mangrove and incompatibility of rehabilitation techniques used with environmental conditions or parameters of the local coastal environment. This study is aimed to analyze the condition of coastal environmental parameters in Bungkutoko island, district of Abeli in rehabilitation proposed of mangrove ecosystem and to find a proper rehabilitation strategy for it can be applied in that area. This study was carried on June to July 2009 in the coastal of Bungkutoko island, Abeli district, Kendari Town. Data in this study is analyzed as descriptively for giving common view of that area. The measurement results of several physical-chemical parameters on the coast of Bungkutoko island at stations I, II and III are suitable for mangrove ecosystem rehabilitation activities, which have a slope of the base: flat and sloping, particle size: small substrate, binding capacity of substrate particles: moderate to loose, confinement coastline: protected and semi protected and open, wave: relatively small, sea level deviation: moderate, tidal type: mixture tends to double daily, current speed: weak, sediment suspension: normal and salinity: 25-35 ppt. Also pay attention to the right planting time on the condition of mangrove tree is in having fruits and calm water condition of sea. And for planting technic is propaguls directly planted to the ground and using seeds on the polybags.